Assessing the current distribution and potential habitat availability for Kaempfer's tody-tyrant: a restricted-range and threatened species from the Atlantic Rainforest - Willrich, Guilherme; Pires Adelino, José Ricardo; Ricardo Bornschein, Marcos [UNESP]; Belmonte-Lopes, Ricardo; Legal, Evair; dos Anjos, Luiz; Lima, Marcos Robalinho (Wiley, 2025)
Human disturbances are threatening biodiversity worldwide, and species with restricted geographic distribution or small population sizes are more likely to become extinct. The prevention of extinctions is an urgent matter and knowledge on the ecology and distribution of threatened species is required to outline conservation strategies. In this study, we investigate the potential and current geographic distribution of the threatened endemic Atlantic Forest bird species Kaempfer's tody-tyrant Hemitriccus kaempferi, to advance conservation efforts for this species. We used a species distribution model (SDM) to assess the potential geographic distribution of the species and to detect environmentally suitable areas to guide field survey efforts. We then established the current geographic distribution of H. kaempferi and estimated the proportion of habitat remaining and how much of it is located within protected areas. We found that suitable areas for H. kaempferi are restricted to low-elevation lands of the south coast of Paraná state and the north and central coast of Santa Catarina state, southern Brazil. The predicted distribution encompasses an area of 7483 km2 of which 44% is currently covered by forest remnants and 15% is inside protected areas. The current geographic distribution was based on 166 occurrence records and encompasses an area of 5898 km2 of which 42% is covered by forest remnants and 13% by protected areas. Coverage of protected areas required to adequately protect the species was estimated as 71% of the predicted area. The species' presence was confirmed in only eight protected areas. Due to its restricted range, great habitat loss, and small coverage of protected areas, conservation actions need to urgently focus on the conservation of remaining forest fragments, habitat restoration programs, the establishment of new protected areas, and citizen awareness.
Keywords: endemic species; environmental niche models; Hemitriccus kaempferi; protected areas; tropical bird conservation; vegetation cover